Divide, Conquer, and Sense: CD8+CD28− T Cells in Perspective - Arosa, Fernando A.; Esgalhado, André J.; Padrão, Carolina A.; Cardoso, Elsa M. (Frontiers in Immunology, 2017)
Understanding the rationale for the generation of a pool of highly differentiated effector memory CD8+ T cells displaying a weakened capacity to scrutinize for peptides complexed with major histocompatibility class I molecules via their T cell receptor, lacking the “signal 2” CD28 receptor, and yet expressing a highly diverse array of innate receptors, from natural killer receptors, interleukin receptors, and damage-associated molecular pattern receptors, among others, is one of the most challenging issues in contemporary human immunology. The prevalence of these differentiated CD8+ T cells, also known as CD8+CD28−, CD8+KIR+, NK-like CD8+ T cells, or innate CD8+ T cells, in non-lymphoid organs and tissues, in peripheral blood of healthy elderly, namely centenarians, but also in stressful and chronic inflammatory conditions suggests that they are not merely end-of-the-line dysfunctional cells. These experienced CD8+ T cells are highly diverse and capable of sensing a variety of TCR-independent signals, which enables them to respond and fine-tune tissue homeostasis.